2016
DOI: 10.1016/j.ibiod.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of aflatoxin-B1 and zearalenone by Streptomyces sp. collection

Abstract: a b s t r a c tAflatoxin B1 (AFB1) and zearalenone (ZON) are hazardous mycotoxins. AFB1 has cytotoxic, mutagenic and carcinogenic effects, whereas ZON can disrupt the endocrine system. Biodegradation by microbes is an effective method to eliminate these hazardous toxins. The aim of this work was to screen AFB1 and ZON biodegrading potential of one hundred and twenty-four Streptomyces strains deposited in the Actinomycetes strain collection of the Department of Environmental Safety and Ecotoxicology. Two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 44 publications
0
33
1
1
Order By: Relevance
“…This new peak was not detected in the presence of the other ten actinobacterial strains (related to Actinomadura, Nocardiopsis and Nonomuraea genera) and in controls (methanol extraction of strains grown in the absence of AFB1). The ability of Streptomyces strains to reduce AFB1 contamination has been reported previously (Zucchi et al 2008;Verheecke et al 2014;Harkai et al 2016). Tests have shown that AFB1 reduction by Streptomyces is not linked to adsorption mechanisms (Verheecke et al 2015).…”
Section: Discussionmentioning
confidence: 75%
“…This new peak was not detected in the presence of the other ten actinobacterial strains (related to Actinomadura, Nocardiopsis and Nonomuraea genera) and in controls (methanol extraction of strains grown in the absence of AFB1). The ability of Streptomyces strains to reduce AFB1 contamination has been reported previously (Zucchi et al 2008;Verheecke et al 2014;Harkai et al 2016). Tests have shown that AFB1 reduction by Streptomyces is not linked to adsorption mechanisms (Verheecke et al 2015).…”
Section: Discussionmentioning
confidence: 75%
“…The mycotoxin degradation ability of different bacteria ( Rhodococcus sp, Streptomyces sp) was previously investigated by this department [ 30 , 37 , 38 ]. Members of the Cupriavidus genus have profound abilities in terms of the biodegradation of different chemicals and xenobiotics, particularly one mycotoxin OTA [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of AFB1, Rhodococcus sp are highly effective biodetoxifiers from 42 type strains of which 15 terminated the genotoxicity in 72 h. With regards to ZON, only one Rhodococcus type strain could terminate the eostrogenic effect [ 30 ]. 124 Streptomyces strains were tested for AFB1 and ZON biodegradation, and only one strain was able to biodetoxify AFB1 and only two strains could terminate the eostrogenic effect of ZON [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to their findings, the mean AFM1 concentration in raw milk samples was 10.7 ± 0.89 ppb, indicating that the raw milk samples exceeded the EU permissible limits (50 ng•L −1 ) and Egyptian standards (50 ng•L −1 ) of AFM1 in milk; the rate of AFM1 detoxification was between 86.1% and 97.7%. In a study, highly active sodium bentonite (SB) soil (SB-E) was used to absorb AF, the results of which showed the maximum The application of enzymes and microorganisms in AF bio-detoxification is a good alternative to conventional techniques in the food industry [189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205] (Figure 5a,b). There are two mechanisms for AF detoxification by microbial methods, these are: cell wall component adhesion and microbial enzymes.…”
Section: Methods Of Aflatoxin Detoxificationmentioning
confidence: 99%